Discrimination of Inrush, Internal, and External Fault in Power Transformer Using Phasor Angle Comparison and Biased Differential Principle. Issue 7 (21st April 2018) - Patel, Dharmesh; Chothani, Nilesh; Mistry, Khyati
Abstract: Conventional protection scheme of power transformer maloperation during abnormalities such as inrush condition, current transformer (CT) saturation during external fault and high resistance internal fault conditions. This article presents inrush detection based on an average angle of 2 nd order derivative of differential current. The magnitude and phase angle of primary and secondary currents are estimated using a Modified Full Cycle Discrete Fourier Transform (MFCDFT) algorithm. Normally, during an internal fault, the differential current is well above the restraining current; however, the same condition arises during external fault with heavy CT saturation. Hence, a phase angle comparison based scheme is combined with percentage biased differential protection. During an internal fault, the phase angle difference of primary and secondary current is <90°, whereas it differs >90° for any external fault conditions. In the proposed scheme, 315 MVA, 400/220 kV transformer is considered for validation of various fault conditions simulated in PSCAD ™ software. Moreover, the proposed scheme is validated on developed laboratory prototype of 2 kVA, 230/115 V single phase transformer using ATmega328 microcontroller. The proposed algorithm is effectively validated on both, simulation and hardware to discriminate inrush, internal and external fault by considering various system and fault parameters.